"Jesus, a porta, Kardec, a chave”: a apropriação do Novo Testamento pelo segmento espírita - Torres, Natália Cannizza (2019)
Towards the arrival of the spiritism in Brazil, many have been the currents adopted by the adherents of this doctrine, within the triple aspect: religious, philosophical and scientific. This research turns to the religious side, focusing on something that arose in the middle of the last century, but gained momentum of propagation in the last decade: the systematized study of the New Testament, that began mainly in Belo Horizonte and has been disseminating nationally. The investigation has been done with the biblical study groups coordinators, mainly from Minas Gerais, but also from São Carlos, a city in the interior of São Paulo which also stands out for the spiritist activity, and where has been done a field research. The research points that the biblical study has been forming a new spiritist structural practice. Through this research we seek to understand the dissemination of this practice as a relevant factor for the big spiritist growth within this decade.